(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
In this research, the computational fluid dynamics (CFD) software FLUENT is used, which employs the finite volume method, to integrate discrete phase models and multiphase flow models in numerical simulations based on a prototype steel ladle from a particular facility. The simulations aim to investigate the slag entrapment phenomenon in bottom argon blowing. The slag layer is filled with DPM (Discrete Phase Model) particles whose densities are consistent with slag. These particles are used to simulate actual non-metallic inclusions in the slag. If the height of a particle is less than the minimum height of the slag layer, it is thought to have been entrained into the molten steel. By using the User Defined Function (UDF), the tracking of this particle is stopped. The simulation results reveal that the slag eyes have a tendency to increase in size as the argon flow rate increases. The slag eyes area is generally small when the argon flow rate is below 500 L/min. However, there is a noticeable increase in the slag eyes area when the argon flow rate exceeds 1000 L/min. The number of particles entrained into the molten steel increases as the argon flow rate increases; the number of particles entering the steel increases gradually below 1000 L/min and dramatically over 1000 L/min.